DENTIFIKASI DAN KARAKTERSASI KANDUNGAN UNSUR DAN STRUKTUR KRISTAL SLAG NICKEL - Asliah Asliah; Suaedi Suaedi; Nururrahmah Hammado; Rahma Hi. Manrulu (Applied Physics of Cokroaminoto Palopo, 2020)
A research has been conducted with the title Identification and Characterization of Elemental Content and Crystal Structure of Slag Nickel. The method used in this research is the aid of XRF test equipment and XRD test equipment to determine the elemental characterization and crystal stucture of nickel slag. The XRF test results showed that the elements contained in the nickel slag were 79.72% Fe, 10.8% Si, 3.14% Cr, 2.23% Mn, 2.04% Ni, 0.74% Ca, 0.56% S, 0.44% Rb, 0.14% Zn , La 0.09%, and Re 0.2%. Then the XRD test results showed that the minerals formed were 79.1% CaMnSiO3, and Fe3O420.9%.